2018
DOI: 10.1002/stem.2804
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous Dissemination of Mesenchymal Stem Cells from Endometriosis

Abstract: Endometriosis is ectopic growth of endometrial tissue traditionally thought to arise through retrograde menstruation. We aimed to determine if cells derived from endometriosis could enter vascular circulation and lead to hematogenous dissemination. Experimental endometriosis was established by transplanting endometrial tissue from DsRed+ mice into the peritoneal cavity of DsRed- mice. Using flow cytometry, we identified DsRed+ cells in blood of animals with endometriosis. The circulating donor cells expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 45 publications
(52 reference statements)
0
28
0
3
Order By: Relevance
“…As haematopoietic cells, all immune cells originate from the bone marrow, and the extensive contribution of immune in endometriosis pathophysiology has been documented. Further, CD45‐ bone marrow‐derived cells in mice are a heterogenous population that includes BM stromal cells, endothelial progenitor cells and mesenchymal stem cells and are identified by their surface markers . CD45‐ cells of BM origin contribute to endometriosis development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As haematopoietic cells, all immune cells originate from the bone marrow, and the extensive contribution of immune in endometriosis pathophysiology has been documented. Further, CD45‐ bone marrow‐derived cells in mice are a heterogenous population that includes BM stromal cells, endothelial progenitor cells and mesenchymal stem cells and are identified by their surface markers . CD45‐ cells of BM origin contribute to endometriosis development.…”
Section: Resultsmentioning
confidence: 99%
“…Here we observed the engraftment of bone marrow‐derived stem cells (BMDSCs), characterized as CD45‐/GFP+/Sca1+, to endometriotic lesions as shown in Figure . While characterized here by immune staining alone, we have previously shown that these engrafted cells can give rise to adipogenic, osteogenic and chondrogenic lineages …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Specifically, CXCL12 is known to drive lymphocyte and macrophage chemotaxis 13,14 in pathophysiological settings of several systems. 15,[17][18][19][20][21][22][23][24][25][26][27] A gradient of CXCL12 is established by secretion from inflammatory environments. This process is known to promote tumour growth and metastasis in at least 20 malignancies.…”
Section: Xcl12mentioning
confidence: 99%
“…15,16 Some examples of the pathophysiological involvement of CXCL12 are depicted and referenced in Table 2 and consist of cancer promotion, reproductive illness to periodontal disease. 15,[17][18][19][20][21][22][23][24][25][26][27] A gradient of CXCL12 is established by secretion from inflammatory environments. Over the past decade, the involvement of chemokines and their respective receptors has been successively elucidated.…”
Section: Xcl12mentioning
confidence: 99%